Nitrogen-doped carbon / V2O3 integrated hierarchical pore composite energy storage material and preparation method thereof
The preparation of nitrogen-doped carbon/V2O3 integrated multi-stage pore composite material through template method and high-temperature thermal decomposition technology, solving the shortcomings of sodium and potassium ion battery anode materials in ion storage and cycle stability, and achieving excellent storage and cycle performance.
Patent Information
- Application Number
- CN202411666279.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-11
AI Technical Summary
The negative electrode materials of existing sodium and potassium ion batteries have shortcomings in ion storage and cycling stability, especially due to the large radii of Na+ and K+ that lead to slow ion movement and irreversible phase transitions during the cycle, resulting in capacity attenuation.
Through the template method, high-temperature thermal decomposition and thermal reduction strategies, a nitrogen-doped carbon/V2O3 integrated multi-stage pore composite material was prepared to form a uniform and stable three-dimensional multi-stage pore structure to improve electron and ion conductivity.
Excellent storage performance and good cycling performance of sodium and potassium ion battery electrode materials are achieved, and volume changes in the ion deintercalation process are buffered, which significantly improves the stability and energy density of the material.
Smart Images

Figure CN119591154A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of vanadium oxide-based energy storage materials, and specifically relates to a nitrogen-doped carbon / V2O3 integrated multi-level pore composite sodium and potassium ion storage material and a preparation method thereof. Background Art
[0002] Currently, the low reserves of lithium resources have caused the cost of lithium-ion batteries (LIBs) to increase gradually, making them less sustainable. Therefore, it is urgent to develop new batteries. Sodium-ion batteries (SIBs) and potassium-ion batteries (PIBs) have many advantages, such as sodium, potassium and lithium have similar chemical properties; sodium and potassium reserves are abundant and low in cost; and K + / K(-2.93 V vs. E 0 ) and Na + / Na(-2.71 V vs. E 0 ) and the standard redox potential of Li + / Li(-3.04 V vs. E 0 ) are close to each other and may become the main substitute for LIBs. Currently, carbon materials with high conductivity and low cost are the most widely used negative electrode materials for LIBs. However, due to the large Na + and K + The slow ion movement, weak cycle stability and low energy density caused by the radius make carbon materials not very suitable as anode materials for SIBs and PIBs. Therefore, it is necessary to develop suitable SIBs and PIBs electrode materials to achieve stable Na + , K + Deintercalation and cycling performance.
[0003] In order to make efficient use of vanadium products and increase the added value of vanadium products, it is of great value to explore the application of vanadium in the field of sodium and potassium batteries. Vanadium oxides have attracted widespread attention in the application of electrode materials due to their high theoretical specific capacity. Among the many vanadium oxides, vanadium oxide (V2O3) has a unique three-dimensional VV skeleton structure that is conducive to Na + , K + Deintercalation. Theoretical calculations show that 1 mol of V2O3 can accommodate 6 mol of Na + , its specific capacity can reach 1070 mAh g -1 However, V2O3 also has some problems in practical applications, such as its low conductivity and slow ion transport, as well as irreversible phase transition and volume expansion during the cycle process, which cause serious capacity decay.
[0004] To address these problems, composite materials with unique structures can be designed by combining with porous carbon materials to improve electronic and ionic conductivity, so as to achieve smaller polarization and good electrochemical performance of the battery. For example, Ren et al. reported the preparation of three-dimensional porous V2O3@C composite materials by NaCl template-assisted freeze-drying technology. The particle size of V2O3 particles in the material was 3-5 nm and was evenly dispersed in the three-dimensional network structure (Electrochimica Acta, 2019, 318, 730-736), which obtained good electrochemical performance as an electrode material for lithium-ion batteries. Park et al. used polystyrene microspheres as templates and combined with carbon nanotubes to prepare three-dimensional porous V2O3-CNT composite microspheres by spray pyrolysis (Small Methods, 2021, 5(9): 2100578). However, these methods require multiple steps, high energy consumption and equipment requirements, which are not conducive to the large-scale production of materials. In addition, the prepared composite materials have obvious interfaces, and the structural stability of the materials is difficult to ensure during the cycle. Therefore, developing new carbon / V2O3 porous composite materials to form a uniform and stable integrated porous composite is beneficial to improving its electrochemical sodium and potassium storage performance. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a nitrogen-doped carbon / V2O3 integrated multi-level porous composite high-performance sodium and potassium ion storage material and a preparation method thereof. The method is based on a template method, high-temperature thermal decomposition and thermal reduction strategy, and the final product is formed into a uniform and stable integrated multi-level porous composite by adjusting the ratio of the vanadium source and the carbon source and the annealing temperature. The method has strong universality, abundant sources of required raw materials, simple operation, low cost, high yield, and is suitable for industrial production.
[0006] The specific technical solution is as follows:
[0007] Nitrogen-doped carbon / V2O3 integrated multi-level porous composite material, the composite material is composed of nitrogen-doped carbon and V2O3 without obvious morphology, and the composite material presents an integrated, three-dimensional multi-level porous structure. The internal micropore diameter of the composite material is 0.6-3.5 nm; the mesopore diameter is 5.3-20 nm; and the macropores are macroscopic. The specific surface area of the composite material is 208-999 m 2 g -1 The composite material has excellent sodium ion (200-350 mAh g -1 ) and potassium ions (110-260 mAh g -1 ) Storage performance.
[0008] The method for preparing the nitrogen-doped carbon / V2O3 integrated hierarchical porous composite material comprises the following steps:
[0009] (1) Preparation of sol precursor:
[0010] Prepare the materials according to the mass ratio of ammonium metavanadate: urea: sodium chloride: carboxymethyl cellulose: water = (0.1~1): (1~2): (10~15): (1~1.5): (100~120), fully dissolve the ammonium metavanadate, urea and sodium chloride in water and mix them evenly. Then slowly add carboxymethyl cellulose and stir slowly with magnetic force until there are no bubbles in the solution and a transparent and uniform sol is formed;
[0011] (2) Preparation of dry gel:
[0012] The xerogel is prepared by freeze drying technology, that is, the sol precursor solution prepared in (1) is slowly poured into a culture dish, first frozen in a freeze dryer, and then dried. The temperature during the freezing process is -60°C to -75°C, and the time during the drying process is 24h to 48h. After drying, the material is fully ground and crushed;
[0013] (3) Calcination treatment:
[0014] The ground dry gel material is calcined at 600-800°C for 2-6 hours under protective gas, cooled to room temperature, and then the product is fully washed to remove the NaCl template, and the final integrated three-dimensional porous nitrogen-doped carbon / V2O3 composite material is obtained by drying.
[0015] In the step (1), the stirring method for fully dissolving ammonium metavanadate, urea and sodium chloride in water is magnetic stirring, the stirring speed is 300 rpm, and the stirring time is 10 to 20 min.
[0016] In the step (1), the stirring method after adding carboxymethyl cellulose is magnetic stirring, the stirring speed is 150 rpm, and the stirring time is 4 to 12 hours.
[0017] In the step (1), the two stirrings are both carried out at room temperature.
[0018] In the step (2), the culture dish is a container made of plastic or low-temperature resistant glass, etc., which can expose the sol to the air over a large area.
[0019] In the step (2), the grinding equipment is a mortar.
[0020] In the step (3), the calcination equipment is a tubular furnace, and the protective gas is N2 or Ar.
[0021] In the step (3), the calcination operating conditions are: heating rate of 5-10°C / min; insulation time of 2h-6h.
[0022] In the step (3), the container for holding the calcined sample is a quartz magnetic boat.
[0023] In the step (3), the cooling method is fan cooling in the tubular furnace.
[0024] In the step (3), the washing solvent is deionized water.
[0025] In the step (3), the drying operation is carried out in a drying oven at a temperature of 60-80° C. for 24-48 hours.
[0026] The basic principle of the present invention is: sodium chloride is used as a three-dimensional template, and the gas generated by the chemical reaction of the reactants is used as a pore-forming agent, so that the final product forms a multi-level porous structure. During the calcination treatment, the reactants undergo many complex chemical reactions: urea as a nitrogen source decomposes at high temperature to provide a nitrogen source doped in the carbon generated by the decomposition of carboxymethyl cellulose; ammonium metavanadate decomposes to first form a V2O5 product, and then is reduced to V2O3 under the reduction of the carbon generated by the decomposition of carboxymethyl cellulose. After these reactions, the nitrogen-doped carbon / V2O3 integrated multi-level porous composite material involved in the present invention is obtained.
[0027] Compared with the prior art, the present invention has the following advantages:
[0028] (1) The raw materials used in the present invention are widely available and low in cost. At the same time, the equipment used in the present invention is simple and easy to operate, avoiding harsh preparation conditions. In addition, the method can prepare materials in large quantities, broadening its application range in the preparation of similar porous composite materials.
[0029] (2) The nitrogen-doped carbon / V2O3 integrated hierarchical porous composite material of the present invention is formed in one step by a complex chemical reaction during the calcination process and does not require any other treatment.
[0030] (3) The nitrogen-doped carbon / V2O3 integrated multi-level porous composite material of the present invention effectively buffers the volume change during the insertion and extraction of sodium and potassium ions, and exhibits excellent cycling performance.
[0031] (4) The nitrogen-doped carbon and V2O3 in the present invention have no obvious interface and exhibit uniform integration characteristics.
[0032] (5) The nitrogen-doped carbon / V2O3 material of the present invention has a multi-level pore characteristic and exhibits a three-dimensional network structure in which the multi-level pores are interconnected, so that the material has a high porosity. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is an X-ray diffraction photograph of the nitrogen-doped carbon / V2O3 integrated hierarchical porous composite material prepared in Example 1;
[0034] Figure 2 This is a scanning electron microscope photo of the nitrogen-doped carbon / V2O3 integrated hierarchical porous composite material prepared in Example 1;
[0035] Figure 3 This is a transmission electron microscopy image of the nitrogen-doped carbon / V2O3 integrated hierarchical porous composite material prepared in Example 1;
[0036] Figure 4 This is a nitrogen adsorption diagram of the nitrogen-doped carbon / V2O3 integrated hierarchical porous composite material prepared in Example 1;
[0037] Figure 5 This is a pore size distribution diagram of the nitrogen-doped carbon / V2O3 integrated hierarchical porous composite material prepared in Example 1;
[0038] Figure 6 This is a scanning electron microscope image of the nitrogen-doped carbon / V2O3 integrated hierarchical porous composite material prepared in Example 2;
[0039] Figure 7 This is a transmission electron microscopy image of the nitrogen-doped carbon / V2O3 integrated multi-level porous composite material prepared in Example 2;
[0040] Figure 8 This is a nitrogen adsorption diagram of the nitrogen-doped carbon / V2O3 integrated hierarchical porous composite material prepared in Example 2;
[0041] Fig. 9 This is a pore size distribution diagram of the nitrogen-doped carbon / V2O3 integrated multi-level porous composite material prepared in Example 2;
[0042] Fig.10 This is a scanning electron microscope image of the nitrogen-doped carbon / V2O3 integrated hierarchical porous composite material prepared in Example 3; DETAILED DESCRIPTION
[0043] The present invention is further described in detail below in conjunction with embodiments.
[0044] (1) XRD was performed using an X-ray diffractometer from Panalytical Empyrean, the Netherlands, with a voltage and current of 40 kV and 40 mA, respectively. The Cu target was used as the emission source to identify the crystal structure and chemical composition of the prepared samples.
[0045] (2) A scanning electron microscope (SU 8010) from Hitachi, Japan, was used to observe the morphology and structural characteristics of the samples.
[0046] (3) A transmission electron microscope (JEM 2100F) from Japan Electron Corporation was used to observe the internal microstructure of the samples.
[0047] (4) Nitrogen adsorption-desorption test was performed using the instrument Autosorb-IQ-MP-C to characterize the surface area and pore conditions.
[0048] (5) The electrochemical test was conducted using a button-type CR2032 half-cell. The electrode sheet was prepared as follows: the material, acetylene black and polyvinylidene fluoride (PVDF) were mixed in a ratio of 8:1:1 and fully ground until the three were evenly mixed. Then, an appropriate amount of N-methylpyrrolidone (NMP) was added to form a slurry, which was evenly mixed by stirring for 12 h and then evenly coated on the surface of the copper foil. Finally, it was dried in a vacuum oven at 60°C for 12 h to completely evaporate the solvent NMP. After drying, the electrode sheet was placed in a hydraulic tablet press for compaction, and then a slicer was used to cut the electrode sheet into a circular electrode sheet with a diameter of 15 mm to obtain the electrode of the sodium ion and potassium ion battery. The electrode sheet was used as the working electrode, the sodium sheet and the potassium sheet were used as the counter electrode, and the diaphragm was a glass fiber membrane. The electrolyte was replaced with sodium ion and potassium ion electrolytes to assemble the battery. After the battery was assembled, it was left for 12 h to ensure that the electrolyte was fully infiltrated before the electrochemical test was performed.
[0049] The chemical reagents used in the embodiments of the present invention are provided by Sinopharm Chemical Reagent Co., Ltd.
[0050] The present invention is described in detail below in conjunction with specific embodiments.
[0051] Example 1
[0052] Preparation of nitrogen-doped carbon / V2O3 integrated hierarchical porous composite materials:
[0053] (1) Prepare the materials in a mass ratio of ammonium metavanadate: urea: sodium chloride: carboxymethyl cellulose: water = 0.5:1:10:1:100, dissolve ammonium metavanadate, urea and sodium chloride in deionized water, stir and mix them evenly, and then slowly add carboxymethyl cellulose to prepare a sol. The sol is magnetically stirred for 12 hours to make it fully and evenly dispersed and form a transparent sol without bubbles;
[0054] (2) Prepare the xerogel using freeze drying technology, that is, slowly pour the sol precursor solution prepared in (1) into a plastic culture dish, freeze it solid at -60°C in a freeze dryer, and then vacuum freeze dry it for 24 hours. After drying, the material is fully crushed in an agate mortar;
[0055] (3) The ground dry gel material was calcined at 700°C in Ar protection at a heating rate of 5°C / min for 4 hours. After the calcination was completed and cooled to room temperature, the product was fully washed with deionized water to remove the sodium chloride template. Then, it was dried in a vacuum drying oven at 60°C for 12 hours to remove moisture, and the final three-dimensional nitrogen-doped carbon / V2O3 integrated hierarchical porous composite material was obtained.
[0056] The X-ray diffraction image of the nitrogen-doped carbon / V2O3 integrated hierarchical porous composite material is shown in Figure 1 As shown, scanning electron microscope photos are shown Figure 2 As shown in the transmission electron microscope picture Figure 3 As shown, the nitrogen adsorption diagram is as follows Figure 4 The pore size distribution diagram is shown in Figure 5 As shown in Figure 2, the specific surface area of the three-dimensional nitrogen-doped carbon / V2O3 integrated hierarchical porous composite material is 208 m 2 g -1 The mesopore diameters are 3.8 nm and 6.1 nm. When used as electrode materials for potassium ion batteries and sodium ion batteries, the composite material can -1 At a current density of 260 mAh g -1 Potassium storage and 350 mAh g -1 Sodium storage capacity. At 1 A g -1 Under high current, the sodium storage capacity is 110 mAh g after 900 cycles. -1 The potassium storage capacity is 123 mAh g -1 .
[0057] Example 2
[0058] (1) Prepare the materials in a mass ratio of ammonium metavanadate: urea: sodium chloride: carboxymethyl cellulose: water = 0.1:1:10:1:100, dissolve ammonium metavanadate, urea and sodium chloride in deionized water, stir and mix them evenly, and then slowly add carboxymethyl cellulose to prepare a sol. The sol is magnetically stirred for 12 hours to make it fully and evenly dispersed and form a transparent sol without bubbles;
[0059] (2) Same as (2) in Example 1;
[0060] (3) Same as (3) in Example 1.
[0061] The scanning electron microscope photo of the nitrogen-doped carbon / V2O3 integrated hierarchical porous composite material is shown in the figure. Figure 6 As shown in the transmission electron microscope picture Figure 7 As shown, the nitrogen adsorption diagram is as follows Figure 8 The pore size distribution diagram is shown in Fig. 9 As shown in Figure 2, the specific surface area of the three-dimensional nitrogen-doped carbon / V2O3 integrated hierarchical porous composite material is 999 m 2 g -1 The mesopore diameters are 3.5 nm and 5.3 nm. When used as electrode materials for potassium ion batteries and sodium ion batteries, the material can -1 The current density of 114 mAh g -1Potassium storage and 234 mAh g -1 Sodium storage capacity. At 1 A g -1 Under high current, the sodium storage capacity is 56 mAh g after 900 cycles. -1 , the potassium storage capacity is 115 mAh g -1 .
[0062] Example 3
[0063] (1) Prepare the materials in a mass ratio of ammonium metavanadate: urea: sodium chloride: carboxymethyl cellulose: water = 0.8:1:10:1:100, dissolve ammonium metavanadate, urea and sodium chloride in deionized water, stir and mix them evenly, and then slowly add carboxymethyl cellulose to prepare a sol. The sol is magnetically stirred for 12 hours to make it fully and evenly dispersed and form a transparent sol without bubbles;
[0064] (2) Same as (2) in Example 1;
[0065] (3) Same as (3) in Example 1.
[0066] The scanning electron microscope photo of the nitrogen-doped carbon / V2O3 integrated hierarchical porous composite material is shown in the figure. Fig.10 As shown. When used as electrode materials for potassium ion batteries and sodium ion batteries, this material has a -1 At a current density of 200 mAhg -1 Potassium storage and 310 mAh g -1 Sodium storage capacity.
[0067] The above embodiments are only used to illustrate but not to limit the technical solutions of the present invention. Any technical solutions that do not deviate from the spirit and scope of the present invention should be included in the scope of the patent application of the present invention.
Claims
1. A method for preparing a nitrogen-doped carbon / V2O3 integrated multi-level porous composite energy storage material, characterized in that: The following steps are involved: (1) Preparation of sol precursor: Prepare the materials according to the mass ratio of ammonium metavanadate: urea: sodium chloride: carboxymethyl cellulose: water = (0.1-1): (1-2): (10-15): (1-1.5): (100-120), fully dissolve the ammonium metavanadate, urea and sodium chloride in water and mix them evenly; then slowly add carboxymethyl cellulose, and slowly stir with a magnetic force until there are no bubbles in the solution and a transparent and uniform sol is formed; wherein: the stirring method is magnetic stirring, the stirring speed is 150-300 rpm, and the stirring time is 4-12h; (2) Preparation of dry gel: The xerogel is prepared by freeze drying technology, that is, the sol precursor solution prepared in (1) is slowly poured into a culture dish, first frozen in a freeze dryer, and then dried; the temperature during the freezing process is -60°C to -75°C, and the time during the drying process is 24h to 48h; after drying, the material is fully ground and pulverized; wherein: the culture dish is a container such as plastic or low-temperature resistant glass products that can expose the sol to the air over a large area; the grinding equipment is a mortar; (3) Calcination treatment: The ground dry gel material is calcined at 600-800°C for 2-6 hours, cooled to room temperature, and then the product is fully washed to remove the NaCl template, and then dried to obtain the final integrated three-dimensional porous nitrogen-doped carbon / V2O3 composite material; wherein: The calcination operation is carried out in a tubular furnace, the protective gas is N2 or Ar, the heating rate of the calcination operation is 5~10℃ / min, the holding time is 2h~4h, the container for the calcined sample is a quartz boat, the cooling method is fan cooling in the tubular furnace, the washing solvent is deionized water, and the drying operation is carried out in a drying oven, the drying temperature is 60~80℃, and the time is 24~48h; The composite material is composed of nitrogen-doped carbon and V2O3 without obvious morphology, and the composite material presents an integrated, uniform, three-dimensional multi-level pore structure; the internal micropore diameter of the composite material is 0.6-3.5 nm; the mesopore diameter is 5.3-20 nm; the specific surface area of the composite material is 208-999 m 2 g -1 ; has excellent sodium ion (200-350 mAh g -1 ) and potassium ions (110-260 mAh g -1 ) Storage performance.
2. The method for preparing the nitrogen-doped carbon / V2O3 integrated multi-level porous composite energy storage material according to claim 1, characterized in that: The integration refers to the formation of a uniform composite material without obvious interfaces by nitrogen-doped carbon and V2O3; the composite material presents a three-dimensional multi-level pore structure.